PEMBUATAN SISTEM INFORMASI ADMINISTRASI BAGIAN WAKAF BERBASIS WEB DI SD IT AL – KHAIRAAT YOGYAKARTA DENGAN PHP MYSQL - Devi Retno Apriliani; Muhammad Sholeh (Jurnal SCRIPT, 2016)
The development of education had been developing along with the advance of technology and information. One of technology that widely used today is website. The existence of website has proven capable to give easiness and can deliver information accurately, effective, and efficient accessible everywhere, anytime, and by everyone. Based on the result of the old system analysis is know that the payment administrator information system at Integrated Islamic Elementary School Al – Khairaat still using manual way, via Microsoft Office Excel. This situation makes administrator having problems, and the condition were not efficient if using manual system. This final project with title Designing Web Based Information System for Wakaf Administration at Integrated Islamic Elementary School Al – Khairaat Yogyakarta Using PHP – MySQL, intend to make an easy way for payment system of wakaf administration